2015
DOI: 10.1038/nrneph.2014.243
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac imaging in patients with chronic kidney disease

Abstract: Patients with chronic kidney disease (CKD) carry a high cardiovascular risk. In this patient group, cardiac structure and function are frequently abnormal and 74% of patients with CKD stage 5 have left ventricular hypertrophy (LVH) at the initiation of renal replacement therapy. Cardiac changes, such as LVH and impaired left ventricular systolic function, have been associated with an unfavourable prognosis. Despite the prevalence of underlying cardiac abnormalities, symptoms may not manifest in many patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 104 publications
0
36
0
Order By: Relevance
“…In addition to superior image quality, MRI is the only imaging modality that can provide a complete and simultaneous assessment of cardiac morphology, cardiac output, global/regional contractile function, fibrosis, coronary artery flow and contrast-free measurement of myocardial perfusion [1]. Haemodynamic instability during dialysis plays a central role in the pathophysiology of cardiac disease.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to superior image quality, MRI is the only imaging modality that can provide a complete and simultaneous assessment of cardiac morphology, cardiac output, global/regional contractile function, fibrosis, coronary artery flow and contrast-free measurement of myocardial perfusion [1]. Haemodynamic instability during dialysis plays a central role in the pathophysiology of cardiac disease.…”
Section: Introductionmentioning
confidence: 99%
“…In this patient group, cardiac structure and function are frequently abnormal and 74% of patients with CKD stage 5 have LVH at the initiation of renal replacement therapy (RRT). Cardiac changes, such as LVH and impaired LV systolic function have been associated with an unfavorable prognosis [11]. To our knowledge this is the first longitudinal study that describes an important and association between the degree of RRF and LVH in PD patients before RRT and after first years of dialysis treatment.…”
Section: Discussionmentioning
confidence: 91%
“…Despite the prevalence of underlying cardiac abnormalities, symptoms may not manifest in many patients. 13 Abnormalities in LV size and function are common in dialysis patients due to a variety of reasons, such as volume overload, anemia, secondary hyperparathyroidism, chronic inflammation, and malnutrition. 14 In a study by Wang et al, 15 they showed that in adult chronic PD patients, the prevalence of LVH was noted to be as high as 94.8%.…”
Section: Discussionmentioning
confidence: 99%